Living Walls in The City : Community Values and Expectations - Rosmina, Ahmad Bustami; Robyn, Rawlings; Simon, Beecham; James, Ward; Darrien Mah, Yau Seng (Penerbit UTHM, 2023)
There is an increasing interest in living walls in the urban environment, particularly when linked into green infrastructure for urban heat island mitigation. However, the social acceptance of such systems in Australia is largely untested. To address this knowledge gap, a survey ofnineteen local government authorities and twentyliving wall owners and managers was conducted.The survey participants included commercial and residential buildings. The survey was used to study living wall owners’ motivations and expectations of living walls as well as the social values attached to the installed infrastructure. This study related the experiences of living wall owners to the current technical knowledge of living walls and contextualised the benefits and costs of living walls for Australian homes and buildings within the public attitudes and motivations for installing such infrastructure. The survey found that social acceptance and the aesthetic values placed on living walls and greenery more broadly represented a substantial advantage for living walls.